Assessment of Freeze-Thaw in Romania - Arion Cristian; Vacareanu Radu; Aldea Alexandru; Arion Andrei; Pavel Florin (E3S Web of Conferences)
Due in part to political participation, the study of severe climate and weather conditions has attracted a lot of attention in recent decades. However, there has been insufficient focus on the historical climate monitoring data. Accurate estimates of frost heave are crucial for determining construction costs, designing building foundations, and ensuring the integrity of concrete structures. Additionally, frost heave plays a significant role in local meteorological conditions, impacting perennial plants. To mitigate the effects of freeze-thaw cycles on concrete, various strategies must be employed during the design, construction, and maintenance phases. The results from this investigation could be applied to mitigate frost-related disasters and inform the development of policies and measures for adapting geotechnical and structural designs to the specific conditions of Romania. Also, the paper presents the calculations of winter severity parameters for the city of Cluj-Napoca. A Romanian freeze-thaw cycle (FTC) map is essential due to recent climate studies showing an increase in both global and local surface temperatures, with the past thirty years seeing the most notable warming.